Multilingualism in Lithuanian Children’s Folklore - Anglickienė Laimutė; Macijauskaitė-Bonda Jurgita (Darnioji daugiakalbystė)
Multilingualism and multiculturalism have always been phenomena present in folklore. Since the last decades of the 20th century, due to changes in lifestyle influenced by factors such as globalization, intense migration, development of social media, and information technologies, manifestations of multilingualism and multiculturalism have become even more noticeable and, in consequence, are becoming an important feature of contemporary folkloric creation. Focusing on a few genres, namely, counting-out rhymes, games, horror stories and horror verses, this article presents and discusses manifestations of multilingualism in Lithuanian children’s folklore. The following are the main research questions that the present study aims to investigate: How does multilingualism manifest in children’s folklore and what functions does it perform? How do children adopt and transmit folklore, i.e. how do they adopt and creatively reinterpret texts and plots, namely, forms and contents from other languages? Which foreign languages have major impact on Lithuanian children’s folklore? The methodology of the research consists of analytical descriptive and comparative analyses. The research has shown that Lithuanian children’s folklore is dynamic and open to other languages and cultures. Children are attracted by linguistic play and feel comfortable with texts containing foreign or unknown words. In Lithuanian folklore, two major influences can be traced: Russian influence, particularly from World War II until the beginning of the 21st century, and influence from English-speaking countries, beginning in the 1990s and continuing to the present. Children translate folklore, sometimes word for word, adapt foreign texts, plots, traditions, take over certain genres, or integrate separate words or phrases from other languages into Lithuanian folklore.